ANALYSIS OF 8P BUSINESS ESTABLISHMENT CAFÉ ASTUNGKARA IN BUMI SERPONG DAMAI - Indra, Febryola; Christabel, Verenia Novelia; Theodore, Albert (Journal of Industrial Engineering & Management Research, 2022)
Astungkara is a cloud kitchen with the theme of food and beverage with traditional Indonesian flavors. The mainstay menus served are food menus that have traditional Indonesian flavors, both those that have been served in Fusion form, and those that are still traditional. The beverage served are drinks that have a traditional Indonesian taste. Astungkara is an expression of religion which means "Pray or Praise". The author hopes that Astungkara praises God’s most perfect creation, namely humans, and the food and beverage served by Astungkara are food and beverage filled with blessings and prayers. In addition. Astungkara itself is a Sanskrit language which means Praise or Pray, where business owners want the food produced by Astungkara to provide good prayers for people who enjoy it.